Workshop Penggunaan Aplikasi SPSS Pada Penelitian Big Data Bidang Akuntansi di Kota Pontianak - Indriani, Ika Kurnia; Prasetyo, Henri; Soraya; Mahyus; Cahyowati, Anik; Widodo, Agus; Rukmi, Murti Puspita; Nugroho, Yohanes Adi; Cahyowati, Perdhiansyah; Nur, Uray M. (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
Improving the quality of accounting research in Pontianak City could be done by increasing students' ability to process big data and operate SPSS applications. The increasingly massive development of technology provides convenience in obtaining entity financial information. The quality of financial information will determine stakeholder policies in the future. The ability of accounting students to process financial data will be an added value in the world of work. This workshop was conducted using two methods; delivering materials and mentoring in practicums. Participants who attended this activity numbered 51 people from accounting students of DIII, DIV, S1, and S2 study programs from Pontianak State Polytechnic and Tanjungpura University. The results achieved from this workshop were increased knowledge and skills of participants in applying the SPSS program for big data processing. At the same time, it produces the ability to identify data types, input data, and process data to interpret SPSS output in the form of descriptions.